Clearance of anal and penile HPV 6, 11, 16, and 18 DNA and antibodies among adolescent men who have sex with men (HYPER): An observational cohort study - Tian Tian; Leiwen Fu; Bingyi Wang; Xinyi Zhou; Yi-Fan Lin; Yanxiao Gao; Yuwei Li; Yinghui Sun; Jianghong Dai; Huachun Zou (Vaccine: X, 2024)
Background: Clearance of human papillomavirus (HPV) among adolescent men who have sex with men (MSM) is not well studied. This study aimed to evaluate the clearance of HPV DNA and antibodies among adolescent MSM. Methods: In our cohort study, we enrolled adolescent MSM in Melbourne between October 2010 and September 2013. At baseline, 3, 6, and 12 months, anal and penile swabs for HPV DNA and serum for HPV antibodies against genotypes 6, 11, 16, and 18, were collected. Definite clearance was defined as HPV DNA (same site) /antibodies for the same genotype undetected following a positive HPV DNA /antibodies test at baseline or month 3. Possible clearance was defined as HPV DNA (same site) /antibodies for the same genotype undetected at month 12 following a positive HPV DNA/antibodies test at month 6. Overall clearance was defined as either definite or possible clearance. The agreement between HPV DNA clearance and antibodies clearance was calculated. Results: A total of 183 MSM were included (median age: 19 years, interquartile [IQR]: 18 to 20). At the anus, overall clearance rate was 21.6 (95 % confidence interval[CI]: 7.9 to 47.0), 44.8 (19.3 to 88.3), 51.9 (20.9 to 106.9) and 33.7 (7.0 to 98.5) per 1000 person months (PM) for HPV 6, 11, 16 and 18. At the penis, overall clearance rate was 64.5 (13.3 to 188.5), 71.3 (14.7 to 208.2), 96.5 (31.3 to 225.3) and 333.3 (8.4 to 1857.2) per 1000 PM for HPV 6, 11, 16 and 18. For antibodies, overall clearance rate was 22.2 (9.6 to 43.7), 18.8 (3.9 to 55.0), 10.8 (0.3 to 60.1) and 19.0 (2.3 to 68.8) per 1000 PM. Agreement between anal/penile HPV DNA clearance and antibodies clearance was low: kappa = -0.18 (95 % CI: −0.28 to 0.08)/-0.13 (−0.24 to −0.02), 0.04 (−0.29 to 0.36)/0.22 (−0.32 to 0.76), −0.10 (−0.27 to 0.08)/-0.14 (−0.37 to 0.10) and −0.14 (−0.28 to 0.01)/-0.14 (−0.33 to 0.06) for HPV 6, 11, 16 and 18, respectively. Conclusion: Clearance rates of HPV DNA were low and varied by genotypes and anatomical sites among adolescent MSM. Antibodies against HPV were stable during the study period.